Maladaptive schemas as a potential mechanism through which irrational beliefs relate to psychological distress in athletes - Turner, M. J.; Aspin, G.; Gillman, J. (Psychology of Sport and Exercise, 2019)
Objectives: The psychological wellbeing of athletes, in particular the concept of psychological distress, is receiving growing research attention. Irrational beliefs as proposed in Rational Emotive Behaviour Therapy (REBT) have been shown to be positively related to the psychological distress of athletes, but the mechanisms by which irrational beliefs predict psychological distress remain unclear. The role of maladaptive schemas, as proposed in Schema Therapy (ST), in the relationship between irrational beliefs and psychological distress has not yet been studied, despite the conceptual similarities between REBT and ST. Design and method: Participants were self-selected triathletes (n = 124), duathletes (n = 9), swimmers (n = 7), cyclists (n = 17) and runners (n = 57). A single timepoint cross-sectional study design was used to investigate simple mediation models using the PROCESS macro. Results: Results revealed that maladaptive schemas fully mediated the positive relationship between irrational beliefs and symptoms of anxiety, and depression (psychological distress). Conclusions: These findings suggest that maladaptive schemas are a potential mechanism through which irrational beliefs predict psychological distress. Results may help practitioners begin to understand how REBT and ST may be applied in tandem for the benefit of greater athlete psychological wellbeing.